Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1055/a-1852-6889
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Glycosyl Chlorides from Thioglycosides Mediated by a Bromodiethylsulfonium Salt as a Mild Oxidant

Abstract: Conventional synthesis of glycosyl chlorides from thioglycosides relies on the two sequential oxidation and chlorination. A one-pot synthesis of glycosyl chlorides is warranted as an alternative method. Herein, we report the one-pot synthesis of glycosyl chlorides from thioglycoside precursors. The transformation was mediated at low temperature by bromodiethylsulfonium bromopentachloroantimonate (BDSB) as a mild oxidant and n-Bu4NCl as an additive. The armed thioglycosides afforded the corresponding α-glycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The intramolecular cyclization via 5- exo -tet of the anomeric oxygen yields the glycosyl intermediate B . These reversible processes are disrupted by chloride ion transfer from the SbCl 5 Br anion, 23,31 which could endure an S N 1-like pathway through an oxocarbenium intermediate or direct displacement of 2-(bromomethyl)tetrahydrofuran (S N 2-like pathway), generating glycosyl chloride. 32 Subsequently, nucleophilic substitution by the glycosyl acceptor forms the desired coupling product.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intramolecular cyclization via 5- exo -tet of the anomeric oxygen yields the glycosyl intermediate B . These reversible processes are disrupted by chloride ion transfer from the SbCl 5 Br anion, 23,31 which could endure an S N 1-like pathway through an oxocarbenium intermediate or direct displacement of 2-(bromomethyl)tetrahydrofuran (S N 2-like pathway), generating glycosyl chloride. 32 Subsequently, nucleophilic substitution by the glycosyl acceptor forms the desired coupling product.…”
Section: Resultsmentioning
confidence: 99%
“…22 Similarly, our research group has recently observed the transfer of chloride ions during the synthesis of α-glycosyl chlorides from thioglycosides using BDSB as a mild oxidant. 23…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generated chlorides were used in subsequent glycosylations in situ . Very recently, a very thorough study by Padungros and co-workers led to the development of a new bromodiethylsulfonium/bromopentachloroantimonate-mediated protocol (Scheme E) . This method is applicable to a broad range of substrates, but due to competing hydrolysis, the yields are moderate at this stage of the method’s development.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, a very thorough study by Padungros and co-workers led to the development of a new bromodiethylsulfonium/bromopentachloroantimonate-mediated protocol (Scheme 1E). 35 This method is applicable to a broad range of substrates, but due to competing hydrolysis, the yields are moderate at this stage of the method's development. As evident from this compendium of previous methods, a majority of existing reaction conditions are applicable for the reactive (armed) thioglycosides and very few are effective for the less reactive (disarmed) counterparts.…”
Section: ■ Introductionmentioning
confidence: 99%